The performance of turbocharged diesel engine with injected calophyllum inophyllum methyl ester blends and inducted babul wood gaseous fuels - Nayak, S. K.; Mishra, P. C.; M. M., Noor; Hagos, F. Y.; K., Kadirgama; R., Mamat (Elsevier, 2019)
The current investigation briefly elaborates usage of calophyllum inophyllum biodiesel and babul-derived gas on a turbocharged diesel engine operated in dual fuel mode taking into consideration two different phases of operation. Initially, the experimentation was to be carried out keeping the gas flow rate fixed at 21.58 kg/h with varying loading condition in contrast to the naturally aspirated mode. Secondly, the gas flow rate was varied for all the fuels with fixed optimal loading conditions at 3.77 kW. Meanwhile, the modified operating parameters such as injection timing (230bTDC), injection pressure (240 bar), combustion chamber (TrCC), nozzle hole geometry (4-hole) were kept constant throughout the set of experimentations. The present work describes the novelty of varying the gas flow rate techniques with modified engine parameters in order to discuss the overall performance, and emission and combustion behavior in contrast to conventional diesel fuel. The result concludes a lower thermal efficiency (BTE) for B20 + P gas (21.58 kg/h) of 2.7%↓ while higher exhaust gas temperature (EGT) and brake specific energy consumption (BSEC) of 3.7%↑ and 2.18%↑ at 3.77 kW than diesel + P gas. Additionally, considering emission analysis, carbon monoxide (CO), carbon dioxide (CO2), hydrocarbon (HC), nitric oxide (NO) and smoke opacity delivers a lower emission range for B20 + P gas of about 24.4%↓, 7.14%↓, 60.8%↓, 14.28%↓ and 42.8%↓ in comparison to diesel + P gas at optimal loading conditions. Moreover, varying the producer gas flow rate depicted a lower BTE and higher BSEC, EGT for B20 at maximum flow rate of 21.58 kg/h was 7.6%↓, 1.7%↑and 6.7%↑ in contrast to conventional fuel. Furthermore, CO, CO2, HC, NO and smoke opacity delivers a very low emission range of 15.2%↓, 8.42%↓, 20.5%↓, 29.6%↓ and 49.3%↓ in contrast to diesel fuel in dual fuel mode. Hence, considering the above discussion, engine with optimal load of 3.77 kW and gas flow rate of 21.58 kg/h along with modified engine parameters as discussed above enhanced the engine’s overall performance. This provides a freedom from using conventional resources resulting in both diesel fuel savings and energy security for future development.